The Indonesian Version of The Poisonous Parenting Style Scale: Development of Measuring Tools and Adaptation - Achmad Syahid; Moh. Irvan; Raden Roro Riefiant Yasmin Randraputri; Sri Rahmawati (LPPM Universitas PGRI Sumatera Barat, 2024)
There is no credible the Indonesian Version of the Poisonous Parenting Style Scale (IVPPSS) that has been published in any scientific work. Parenting practices that have a negative, even toxic, impact on children’s psychological dimensions are perhaps generally practiced without realizing it. The use of the term poisonous parenting, often used interchangeably with toxic parenting by toxic parents, has a negative impact on children’s mental development and psychological well-being. This parenting style can also have a negative impact on children’s mental health, development, achievement and adjustment. This prompted researchers to develop the poisonous parenting style scale instrument. Based on the results of psychometric testing, it shows that the IVPPSS is a fit model with the data. The poisonous parenting style scale measuring tool has three dimensions, namely the pageant parent, the dismissive parent and the contemptuous parent. There are 16 valid items to measure the construct of the pageant parent, the dismissive parents and the contemptuous parent. Furthermore, there are 5 valid items measuring factors from the pageant parent dimension, 5 valid items measuring factors from the dismissive parent dimension, and 6 valid items measuring the contemptuous parent factor. Overall, the results of this research provide initial evidence to support the IVPPSS as a measuring tool that has conceptual and psychometric strength.